Using Cash Flow Ratios To Establish A Manufacturing Bankruptcy Prediction Model - M. Sienly Veronica; Ida Ida; Vincent Tanu Winata (Jurnal Manajemen Indonesia, 2020)
This research has the purpose of forming a bankruptcy prediction model that will occur in manufacturing companies that listed in Indonesia Stock Exchange using the ratioof cash flow because the manufacturing industry plays an important role in a country's economic development. Cash flow ratio and condition of financial difficulties are used as research variables .Non probabilistic sample with the type of purposive sampling is referred to as the method used in sampling at this research, because rather than the number of manufacturing companies used was 92 manufacturing companies.The methodof data analysis in this research uses logistic regression and the results show that cash flow ratios can predict financial distress with operating cash flow margin is most useful in predicting financial difficulty.These findings can make manufacturing companies focus on cash flow ratios to avoid financial distress. Keywords: cash flow ratios; logistic regression; manufacturing industries; financial distress